Knowledge as a Factor Associated with Lifestyle in Controlling Hypertension - Iriana, Pramita; Yardes, Nelly; Sudrajat, Ace; Mahanani, Munifah Syamara; Malau, Paulus Hotmatua (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Hypertension is also understood as the